Effect of waste wax and chain structure on the mechanical and physical properties of polyethylene - AlMaadeed, M.A. (2015)
The influence of adding waste wax, produced as a by-product of the low density polyethylene manufacturing process, on the thermal and mechanical properties of three types of polyethylene (PE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE) and low-density polyethylene (LDPE), with 10, 20, 30 and 40wt.% was investigated. Polymer–wax mixing was effective with no apparent leakage of the wax during sample preparation, which was evident from the agreement between the theoretical and experimental values of enthalpy for all types of PE.The wax dispersion in the matrix strongly depends on the percentage of wax added to the polymer and the molecular structure of the polymer. It was found that increasing the wax content enhances the phase separation. LDPE undergoes less phase separation due to its highly branched structure composed of a network of short and long chain branches. The wax has no pronounced plasticising effect on the polymer. This is clearly manifested in LDPE as no change in the melting temperature occurred. LLDPE and HDPE were slightly affected by a high concentration of wax (30% and 40%). This is due to the non-uniform distribution of short chain branching along the LLDPE and HDPE main chains, which can interact with the wax structure.